2014
DOI: 10.1016/j.engappai.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Bridging control and artificial intelligence theories for diagnosis: A survey

Abstract: Diagnosis is the process of identifying or determining the nature and root cause of a failure, problem, or disease from the symptoms resulting from selected measurements, checks or tests. The different facets of this problem and the wide spectrum of classes of systems make it interesting to several communities and require bridging several theories. Diagnosis is actually a functional fragment in fault management architectures and it must smoothly interact with other functions. This paper presents diagnosis as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 97 publications
(105 reference statements)
0
44
0
Order By: Relevance
“…Hypothesis testing combining model-based FDI with statistical change detection and testing with methods from artificial intelligence could be employed to avoid nuisance alarms on-board. Such methods were covered in the survey by [31] and a study of data driven diagnosis showed design for isolability of different types of faults in automotive engines [32]. The same authors suggested an explicit comparison of the probability distribution of the residual, estimated online using current data, with no-fault residual distributions in [33] and found that tiny faults, i.e.…”
Section: Detection Behaviour For Incipient Faultsmentioning
confidence: 99%
“…Hypothesis testing combining model-based FDI with statistical change detection and testing with methods from artificial intelligence could be employed to avoid nuisance alarms on-board. Such methods were covered in the survey by [31] and a study of data driven diagnosis showed design for isolability of different types of faults in automotive engines [32]. The same authors suggested an explicit comparison of the probability distribution of the residual, estimated online using current data, with no-fault residual distributions in [33] and found that tiny faults, i.e.…”
Section: Detection Behaviour For Incipient Faultsmentioning
confidence: 99%
“…where the state vector x(t), the input vector u(t), and the output vector y(t) are vectors of continuous variables, and the behavioral model f and the observation model g are functions of the input and state vectors [136]. As many laws of physics are DAE:s, this type of model can with high precision capture the behavior of dynamic mechanical, hydraulic, and electrical systems.…”
Section: Fault Detection and Isolationmentioning
confidence: 99%
“…For thorough reviews of the FDI approach, see e.g. [22,64,136,137]. A typical FDI model describes the nominal behavior of the system using a state space model of differential algebraic equations (DAE:s):…”
Section: Fault Detection and Isolationmentioning
confidence: 99%
“…Within the field of artificial intelligence, model-based diagnosis, sometimes denoted DX, focuses more on fault isolation and the use of logics to identify faulty behavior, see for example (Reiter, 1987), (de Kleer and Williams, 1987), (Feldman andvan Gemund, 2006), and(de Kleer, 2011). A number of papers compare the different approaches from FDI and DX to bridge and integrate methods from the two fields (Cordier et al, 2004;Travé-Massuyès, 2014). In this thesis, diagnosis systems are considered where fault detection is mainly performed using methods from the FDI community and fault isolation is performed using methods from the DX community, see for example (Cordier et al, 2004).…”
Section: Model-based Diagnosismentioning
confidence: 99%